PENGUSAHAAN DAN KELEMBAGAAN LAHAN PERTANIAN DI BERBAGAI AGROEKOSISTEM (KASUS DESA-DESA PATANAS) - Supadi, Supadi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2008)
In trying to get his land the farmer must consider the technical problem, economical and social the culture, the exploitation of agriculture always was linked with what will be produced, how many, here, when, how and where is distributed him. The utilization of the farmer's land as the production factor that was most important in the farming really was influenced by the relations kind between humankind and his land because will be related to in continuation of his farming. The land that was made an effort to get could take the form of his property personally or property of the other person. This research was aimed at identifying and analyzing the exploitation and institutional the agricultural land in rural areas. The method used was survey that was carried out in 12 Patanas villages that were spread in Lampung, West Java, Central Java, East Java, South Sulawesi, and NTB. In three villages, 25 farm households were selected. Results of the research showed the growth index reached 200 to 300, except in the paddy-field land where its irrigation was rotated and in dryland that was cultivated with cassava. The farmer used the superior variety seed, but did not yet apply balanced fertilizing. Fertilizing exceeded the recomendation whereas for other fertilizer (P05 and K20) and relative manure utilization was still under recommendation, in fact some farmers did not use. The productivity of the crop in the rainy season (rice and corn) higher was compared to dry season, except for the potato. Generally the farmer used capital personally, “YARNEN” system was an alternative that often was followed. The price of agricultural product was fluctuating in which the price of the dry season tended to be higher than in the rainy season, the status of the farmer was dominated by owner followed by the sharecropper and the leaser. The sharecropper and the leaser always did not come from the group landless because of the owner, also entered the rented market and sharecropper. The rented system that more stressed the aspect of economics than social more prominent in production centers of the potato.